Global Sensitivity Analysis of the Perniö test embankment - Numerical study on the Creep-SCLAY1S model parameters - ALIKHANZADEH ALAMDARI, Behrang; LARSSON, Simon (My University, 2021)
Construction of railway embankments on soft soil can be a complex problem. Several numerical models have been proposed to evaluate the behaviour of embankments on soft soils. However, several uncertainties arising from the models used and the underlying experimental data remain. These uncertainties find their origin in the non-linear hydro-mechanical response of (soft) soils, that is affected by the loading history. In this thesis, factorial design is used to quantify the most significant model parameters of Creep-SCLAY1S model which have the most influence on the (predicted) stability of the Perniö Embankment. The study concludes that the parameters connected to destructuration and compressibility of natural clays are important when dealing with slope stability of an embankment on soft soils. Furthermore, the study shows that a maximum of 40 % increase and 44 % decrease would be predicted numerically if the magnitude of the evaluated parameters are altered around 15 % of their centre value. It is also argued that more triaxial tests in extension should be performed for this type of geotechnical problem that leads to a shallow failure plane.
Keywords: Fractional factorial design; Full factorial design; Python; pyDOE2; Design of Experiments; Perniö; Failure test; Embankment; Creep-SCLAY1S; PLAXIS